2012
DOI: 10.1111/lre.12009
|View full text |Cite
|
Sign up to set email alerts
|

Occurence of Culturable Vibrio cholerae from Lake Victoria, and Rift Valley Lakes Albert and George, Uganda

Abstract: Vibrio cholerae, a bacterium that causes cholera, poses a human health risk when consumed via untreated or contaminated water. Monthly investigations into the presence of V. cholerae from Lakes Albert, George and Victoria were conducted, with the goal being to examine the relationship between the occurrences of V. cholerae with various water quality parameters at fish landing sites in major water bodies in Uganda. The pH, temperature and electrical conductivity were measured at three fishing sites in each of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Hence, more efforts are required to promote safe water access in Uganda to attain the WHO cholera elimination target [25] and SDG 6 by 2030 since 26% (36/135) of mean physicochemical water tests did not meet WHO drinking water quality standards [53]. These findings together with those of the previous studies which demonstrated the presence of pathogenic V. cholerae in the same water sources [22,23,76] should guide stakeholders to improve access to safe water in the Great Lakes basins of Uganda holistically. Thus, measures such as promotion of use of safe water (using water disinfection), health education, sanitation improvement and hygiene promotion that address both the water bacteriological contents and physicochemical parameters should be considered in both the short and medium terms.…”
Section: Discussionmentioning
confidence: 57%
“…Hence, more efforts are required to promote safe water access in Uganda to attain the WHO cholera elimination target [25] and SDG 6 by 2030 since 26% (36/135) of mean physicochemical water tests did not meet WHO drinking water quality standards [53]. These findings together with those of the previous studies which demonstrated the presence of pathogenic V. cholerae in the same water sources [22,23,76] should guide stakeholders to improve access to safe water in the Great Lakes basins of Uganda holistically. Thus, measures such as promotion of use of safe water (using water disinfection), health education, sanitation improvement and hygiene promotion that address both the water bacteriological contents and physicochemical parameters should be considered in both the short and medium terms.…”
Section: Discussionmentioning
confidence: 57%
“…The absence of V. cholerae O1 suggests that although cholera outbreaks are common in the communities near the major lakes and rivers in Uganda, these lakes may not be the source of pathogens for repeated cholera outbreaks and are unlikely to be reservoirs for V. cholerae O1 as pointed out in earlier studies in sub-Saharan Africa ( Bompangue Nkoko et al, 2011 ; Kaddumukasa et al, 2012 ) that used less definitive methods for pathogen detection. It seems more likely that the observed cholera outbreaks in Uganda could be due to other factors, such as human interaction from cholera endemic communities and outbreak affected areas leading to cross-border infections ( Baluku et al, 2015 ; Bwire et al, 2016 ), traveling from cholera affected areas as happened in Juba, South Sudan ( Ujjiga et al, 2015 ), since most of affected area were along busy international crossing points but also climatic factors could have contributed ( Rebaudet et al, 2013 ).…”
Section: Discussionmentioning
confidence: 93%
“…One possible hypothesis is that the observed distribution of cholera along the major lakes in Uganda is that the lakes and the other surface water sources (rivers, wells, ponds, etc.) are environmental reservoirs for pathogenic V. cholerae responsible for cholera epidemics, as documented in Asia ( Cabral, 2010 ; Wang et al, 2010 ; Lutz et al, 2013 ; Dalusi et al, 2015 ), and in epidemiological studies conducted in sub-Saharan African ( Bompangue et al, 2008 ; Bompangue Nkoko et al, 2011 ; Kaddumukasa et al, 2012 ). It is possible that due to poverty, low level of awareness and inadequate access to safe water and sanitation, communities located along these surface water sources use water from these surface water sources without disinfection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Water temperature, pH, electrical conductivity, and dissolved oxygen potentially regulate V. cholerae [20,37,38]. Over the 2007-2012 period, these parameters were measured twice per month in surface water collected in the lake near Ishungu.…”
Section: Physico-chemical Characteristics Of Lake Kivumentioning
confidence: 99%